Oxidative stress, the blood-brain barrier and neurodegenerative diseases: The critical beneficial role of dietary antioxidants - Jin Feng; Youle Zheng; Mingyue Guo; Irma Ares; Marta Martínez; Bernardo Lopez-Torres; María-Rosa Ma; Xu Wang; Arturo Anadón; María-Aránzazu Martínez (Elsevier, 2023)
In recent years, growing awareness of the role of oxidative stress in brain health has prompted antioxidants, especially dietary antioxidants, to receive growing attention as possible treatments strategies for patients with neurodegenerative diseases (NDs). The most widely studied dietary antioxidants include active substances such as vitamins, carotenoids, flavonoids and polyphenols. Dietary antioxidants are found in usually consumed foods such as fresh fruits, vegetables, nuts and oils and are gaining popularity due to recently growing awareness of their potential for preventive and protective agents against NDs, as well as their abundant natural sources, generally non-toxic nature, and ease of long-term consumption. This review article examines the role of oxidative stress in the development of NDs, explores the 'two-sidedness' of the blood-brain barrier (BBB) as a protective barrier to the nervous system and an impeding barrier to the use of antioxidants as drug medicinal products and/or dietary antioxidants supplements for prevention and therapy and reviews the BBB permeability of common dietary antioxidant suplements and their potential efficacy in the prevention and treatment of NDs. Finally, current challenges and future directions for the prevention and treatment of NDs using dietary antioxidants are discussed, and useful information on the prevention and treatment of NDs is provided.